Pelaksanaan Pembelajaran Seni Budaya Melalui Tatap Muka Terbatas di SMAS Salafiyah Babussalam - Muhassar Sidiq; Robby Ferdian (FBS Padang State University, 2023)
This study aims to find out how forms of implementation of cultural arts learning through limited face-to-face meetings and find the best solutions in overcoming problems in new learning methods. This type of research is qualitative research with a case study method. The research instrument is the researcher concerned and with the help supported by supporting instruments which include tools for taking pictures or photos (cameras), file or data storage tools (flash drives), and stationery. The data in this study there are primary data and secondary data. Interviews, literature studies, and observations are activities carried out in data collection techniques. The steps to analyze the data are data reduction, data presentation and conclusion. Based on what was obtained, the research showed that the process of learning arts and culture through limited face-to-face sessions in class XI IPS SMAS Salafiyah Babussalam was quite good. Even though there are limitations in learning media, the teacher teaches music learning material to follow the flow, where the teacher provides music material using a gradual way to adjust the level of a student's capacity to receive material even though the learning time is relatively short. However, there are obstacles that make it difficult to achieve the final results or learning objectives properly due to the lack of learning time, as well as the unavailability of musical instruments to support the practical learning process, so the teacher only uses the lecture method during material delivery. However, learning outcomes are not too bad because students' interest in learning and students' desire to explore the material is very high even though the learning is monotonous, when viewed from the results obtained based on daily test activities which are quite good.